Does Google shape what we know?. (1st June 2014) - Schroeder, Ralph
Abstract : While much has been written about the technological, economic and regulatory aspects of search engines, their impact on everyday life has been largely overlooked. This essay argues that this is mainly because the role of information and knowledge has been poorly theorized in the social sciences in terms of how search engines are actually used. One way to make a start on this topic is to bring to bear two theoretical frameworks from the social study of technology – large technological systems and the domestication of technology. These allow us to see how search engines have become an infrastructure at a time when, on the one hand, the uses of the Internet as a system have become pervasive and, on the other, information seeking in the home has become a routine activity in everyday life. Several studies of search behaviour have identified the main patterns of search. What emerges is the dominant role played by Google, and that the vast majority of searches are related to leisure. The paper asks whether Google plays a gatekeeping function, and how it shapes the information we use in everyday life.